Evolution of territorial planning in Peru 1920-2021: a historical approach (2022)
Territorial planning in Peru is a political policy that has gone through a winding process throughout seven decades without having been consolidated as a guiding instrument for the development of Peru. The objective of this study was to analyze the planning process in the country over time, paying special attention to the achievements and deficiencies it has presented throughout its history. The methodology used in the study was based on documentary and normative review. The analysis shows that the planning process in Peru has developed in four important periods, called incipient, apogee, crisis and restart, each of which is intrinsically linked to the political and socioeconomic events of the country.